Weihnachtsausstellung : 1993. - Kunsthalle Bern, Bern (Bern : Kunsthalle Bern, 1993)
Abt, Patricia ; Adeyemi, Joseph ; Annen, Giro ; Aschwanden, Edi ; Azzi, Andrea ; Balzli, Berta ; Bärtschi, Marie ; Baumann, Marianne ; Berger, Babette ; Böniger, Elsbeth ; Brülhart, Franz ; Brunner, Claire ; Chablais, Vincent ; Cortese, Dario ; Danz, Pascal ; Dill, Eduard ; Egger, Heinz ; Elsaesser, Caroline ; Feller, Beat ; Fischer, Alexander ; Fivian, Martin ; Freuler, Arthur ; Gassner, Heidi ; Gertsch, Silvia ; etc.
Weihnachtsausstellung 1993, Kunsthalle Bern, 11.12.1993 - 6.1.1994
boek